TEACHERS’ CREATIVITY IN DESIGNING LEARNING ACTIVITIES: SUSTAINING STUDENTS’ MOTIVATION - Lailatul Khikmah (University of Kuningan, 2019)
Sustaining students’ motivation during teaching and learning process, unquestionably, is considered as the most challenging task. Therefore, the teachers have to be mindful and creative in designing an activity as it is the core of the lesson. However, in practice, some teachers are sometimes found to aimlessly use an activity as they run out of idea. Thus, this study is conducted to serve as a reference for the teachers in designing a specific activity that helps the students stay motivated. A descriptive qualitative was employed as the research design to gain deeper analysis on types of activity that encourage the students to learn English. The data were collected through interview which involved 5 professional English teachers as participants. The result revealed that the design of the activity should be appealing and correspond to the students’ interest, age, level of proficiency, school policy, materials and media availability. Thus, it is suggested that the teachers should be brave to try out new activity and attend some teachers’ training, such as CELTA or DELTA, to improve their teaching skills.